Pemanfaatan Daun Kumis Kucing (Orthosiphon Spicatus B.B.S.) sebagai Antiglaukoma - Siska, Siska; Sunaryo, Hadi; Jamaliah, Jamaliah (Fakultas Farmasi Universitas Andalas, 2012)
The effect of the ethanolic extract of Orthosiphon spicatus leaves on the intraocular pressure of glaucoma rats have been investigated. Glaucoma was induced by treating the animal with prednisolone acetat eyedrop 1% every 5 minute for one hour. A number of 30 rats were divided into 6 group. Three groups of animals were treated with the extract at doses of 12, 36, and 108 mg/200 g BW orally. As comparison, a group of normal control animals, a group of negative control animals and another treated with acetazolamide (4,5 mg/200 g bw) were used. Results showed that the extract reduced intraocular pressure of glaucoma rats especially at dose of 36 mg/ 200 g BW.